Pensions, household saving, and welfare: A dynamic analysis of crowd out. Issue 1 (March 2016) - Blau, David M.
Abstract : This paper specifies a life cycle model of saving and employment and uses it to analyze crowd out of private household saving by public and private pensions. Some parameters of the model are estimated and others are calibrated to match life cycle employment and asset profiles, and Social Security claiming decisions. Simulation results indicate that defined benefit (DB) and defined contribution (DC) pensions on average crowd out household wealth by 0.09 and 0.37 per dollar of pension wealth, respectively, while crowd out by Social Security is 0.56. The magnitude of crowd out is sensitive to model specification, with more restrictive versions of the model (e.g., no employment decision, no bequest motive, no uncertainty) generally resulting in larger simulated crowd out. A welfare analysis implies that DB pensions and Social Security are not valued by households. The longevity insurance provided by such plans is offset by a high degree of impatience and, for Social Security, low benefits relative to taxes paid. A typical DC pension is valued at about one quarter of its expected present discounted value.